Peluang Manfaat Ekonomi Kerjasama Pemerintah dan Swasta (KPS) dalam Pengelolaan Tempat Pengolahan Akhir Sampah - Setyoadi, Nino Heri (Jurnal Sosial Ekonomi Pekerjaan Umum, 2009)
Public Private Partnership (PPP) in waste disposal management has been conducted in several areas. This partnership occurs either because of the economic benefits generated from the wated disposal management in this location. This paper describes the intended economic benefits of partnership opportunities between the goverments and private sector in the waste disposal management in Suwung Denpasar and Sumur Batu Bekasi. Data collection method was done by in-depth's interview's, FGD and field observations. For analysis method was using a simple financial calculation such as calculated income for the products of the waste disposal management. Result of calculation indicated a change of economic benefit waste products in both waste disposal. Posibility of economic benefits should be able to optimized in the implementation. Challenges are long procedures and mechanisms to get this opportunity for Certificate of Emision Reduction (CER). If this opportunity optimized, the revenue and profit results of processing the waste products can be used to improve waste services in both regions.